Freelipiniana malayang pagbasa sa panahon ng pandemya [electronic resource] (University of the Philippines Institute of Creative Writing, 2020)
As libraries continue to be inaccessible due to COVID19, the people?s access to reading materials remains limited. This is especially true for Filipiniana selections which are prized for their cultural and intellectual value, but are largely unavailable now because many have not yet been digitized and opened for online access. The Freelipiniana Online Library seeks to bring Filipiniana literature to every Filipino in a time when information and education are limited. All works here are volunteered for distribution by authors and publishers, and cannot be printed, reproduced, or sold without permission from the owner. If you are an author and wish to contribute your work, you may review the guidelines here. If you are a reader, we hope you make use of the available Filipiniana in our online library.